Strategic thinking, deterrence and the US ballistic missile defense project from Truman to Obama - Steff, Reuben (Ashgate, 2013)
This volume is a systematic critical survey of American strategic thinking and the strategic culture in which it is formed. In particular it seeks to interrogate the theory and strategy of nuclear deterrence, and its relationship to the concept of missile defence.